Die Kunst der Diagrammatik: Perspektiven eines neuen bildwissenschaftlichen Paradigmas - Schmidt-Burkhardt, Astrit (transcript, 2017)
The current discourse around diagrams is being shaped not least by the rapid cyclical upswing of graphic representations in art. This book questions the historical prerequisites which are behind the large interest in diagrammatical forms of visualisation and argumentation. Through a diverse range of case studies and theoretical analyses, the diagrammatical potential for image-driven understanding is examined from multiple perspectives. In doing so, the book also explores the future promise of diagrammatology as an autonomous area of visual culture research.